Opposition and resistance: Governance challenges around urban growth in China and the UK - John Sturzaker; Giulio Verdini (Journal of Urban Management, 2017)
This paper proposes that, different though they are, the processes of urban development in China and the UK can be analytically compared by looking at the commonly occurring opposition and resistance to that development. Such opposition and resistance can delay and limit the development of land in and immediately surrounding cities. The paper firstly reviews literature on opposition and resistance to development in both the UK and China, before going on to suggest that this opposition and resistance can in part be explained by a common cause - resentment at opaque and top-down/centralised planning processes. Consequently, the paper concludes that a common solution may applicable in both contexts - increasing participation and building institutional/civic capital amongst communities - and considers the likelihood of implementing this solution, particularly in China.
Keywords: 710; Civic Culture; Metagovernance; Participation; Social capital; Urban growth